Randomized controlled trial comparing outcome of use of staples and nylon sutures for closure in elective orthopedic surgery - Chaudhary, Pashupati; Shrestha, B P; Khanal, G K; Rijal, R; Maharjan, R (Health Renaissance, 2017)
Background: Wound complications are one of the major sources of morbidity after orthopaedic procedures and can prolong the inpatient stay or lead to re-admission. The most commonly used methods for skin closure after orthopaedic surgery are metal staples or nylon sutures Both methods act to hold the skin edges together while healing occurs. Metal staples are said to be superior as they are regarded as quicker as and easier than sutures. Objective: To compare outcome of use of staples and nylon sutures for wound closure in elective orthopedic surgery in term of infection rate,cosmetic appearance(Scar), time taken for skin closure. Methods: It is randomised controlled trial done on patients undergoing elective orthopaedic surgery at department of Orthopaedics at BPKIHS were included in the study. During procedure patients were evaluated for time taken for suture application or any complications. Results: A total of 60 patients (38 male and 22 female) were included in the study. Twenty two patients were between 41-55 years age group followed by fifteen patients between 25-40 yrs, twelve patients less than 25 age group and eleven patients more than 55 years. The average blood loss is 5 ml in K-wire group and 145 ml in plate group. The procedure time is 33 mins as comprared to 53 mins in plate group. Conclusion: Metal staples are superior as they are regarded as quicker and easier than nylon sutures. But use of metal staples or clips has a greater risk of wound infection and less acceptable cosmetically than sutures. Metal staples are more expensive. Health Renaissance 2015;13 (3): 137-143